2012
DOI: 10.1002/pon.3039
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term psychological distress in women at risk for hereditary breast cancer adhering to regular surveillance: a risk profile

Abstract: On the basis of the identified risk profile, it is possible to identify vulnerable women at an early stage, who then may be offered additional and individually tailored support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
3
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 31 publications
5
38
3
6
Order By: Relevance
“…51 Similar to the Meiser review, 34 those data also supported the use of baseline screening to identify risk factors for future distress, including current high distress levels, the presence of unresolved grief, passive coping styles, higher breast cancer risk perception, and greater frequency of breast selfexamination. 51 However, in some studies, an increase was observed in long-term distress among BRCA1/BRCA2 carriers. A 5-year prospective study by Graves et al demonstrated that women who were BRCA1/BRCA2 carriers reported greater genetic testing distress 91 measured according to the Multidimensional Impact of Cancer Risk Assessment (MICRA) questionnaire 92 regardless of their cancer status.…”
Section: Long-term Psychiatric/psychological Impact Of Testingmentioning
confidence: 70%
See 4 more Smart Citations
“…51 Similar to the Meiser review, 34 those data also supported the use of baseline screening to identify risk factors for future distress, including current high distress levels, the presence of unresolved grief, passive coping styles, higher breast cancer risk perception, and greater frequency of breast selfexamination. 51 However, in some studies, an increase was observed in long-term distress among BRCA1/BRCA2 carriers. A 5-year prospective study by Graves et al demonstrated that women who were BRCA1/BRCA2 carriers reported greater genetic testing distress 91 measured according to the Multidimensional Impact of Cancer Risk Assessment (MICRA) questionnaire 92 regardless of their cancer status.…”
Section: Long-term Psychiatric/psychological Impact Of Testingmentioning
confidence: 70%
“…90 The 5-year study included carriers, most of whom (91%) had undergone prophylactic surgery, which may have confounded the results. 90 However, another study of women who were at risk for hereditary breast cancer but who had not undergone prophylactic risk-reducing surgeries reported distress levels that were lower or similar to their baseline levels 5 to 8 years later 51 ; and all long-term distress was predicted by corresponding baseline levels of intrusion, avoidance, anxiety, and depression. 51 Similar to the Meiser review, 34 those data also supported the use of baseline screening to identify risk factors for future distress, including current high distress levels, the presence of unresolved grief, passive coping styles, higher breast cancer risk perception, and greater frequency of breast selfexamination.…”
Section: Long-term Psychiatric/psychological Impact Of Testingmentioning
confidence: 98%
See 3 more Smart Citations